2008
DOI: 10.1021/bc800222e
|View full text |Cite
|
Sign up to set email alerts
|

HPMA as a Scaffold for the Modular Assembly of Functional Peptide Polymers by Native Chemical Ligation

Abstract: Synthetic peptides are valuable tools in fundamental and applied biomedical research. On one hand, these molecules provide highly efficient access to competitive inhibitors of molecular interactions and enzyme substrates by rational design. On the other hand, peptides may serve as powerful vectors to mediate cellular uptake of molecules that otherwise enter cells only poorly. The coupling of both such functionalities provides access to molecules interfering with molecular processes inside the cell. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Following our procedure published previously (Ruttekolk et al, 2008), the BH3 peptide, containing an uncapped N-terminal cysteine residue, was coupled to an active ester-activated HPMA polymer by native chemical ligation (Scheme 1). A conjugate containing only fluoresceinlabeled cysteine-lysyl moieties and a conjugate carrying a mutated BH3 peptide, in which three residues were replaced for alanines, were used as negative controls.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following our procedure published previously (Ruttekolk et al, 2008), the BH3 peptide, containing an uncapped N-terminal cysteine residue, was coupled to an active ester-activated HPMA polymer by native chemical ligation (Scheme 1). A conjugate containing only fluoresceinlabeled cysteine-lysyl moieties and a conjugate carrying a mutated BH3 peptide, in which three residues were replaced for alanines, were used as negative controls.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous analyses had shown that coupling of peptides to an HPMA polymer by native chemical ligation yielded bioactive conjugates by a modular design (Ruttekolk et al, 2008). These initial analyses had already indicated that the polymer-coupled peptides had a higher activity per peptide moiety.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A thioesteractivated HPMA copolymer (28.5 kDa) served as the linear scaffold for the coupling of peptides. [17] We have previously shown that for a dextran backbone functionalized with apoptosisinducing BidBH3 peptides, a multivalent display of peptides yielded increased activity, even inside the cell. [18] However, it has not been explored whether such a molecular design can also act as a scaffold for promoting protein cluster formation in cellular signaling.…”
Section: Resultsmentioning
confidence: 98%